Polymorphism study of MTHFR 677C?T and its correlation with oxidative stress and their influence on female infertility in Erbil – Iraq (Baghdad Science Journal, 2017)
This research includes a study of Methylenetetrahydrofolate reductase gene’s allele 677C?T and its correlation with oxidative stress and their impact on female infertility. Fifty infertile women with the range age (23-42) years and twenty five fertile women with the range age (22-39) years as control group living in Erbil city were selected. The serum level of Malondialdehyde (MDA), superoxide dismutase (SOD), prolactin hormone (PRL), Luteinizing hormone (LH), Thyroid stimulating hormone (TSH), Triiodothyronine hormone (T3), and Thyroxine hormone (T4) were measured, also a body mass index (BMI) was calculated. A restriction enzyme (Hinf1) was used to improve the mutation in DNA bands of infertile women. The results showed significant increases in MDA level, SOD activity, BMI, PRL, LH, TSH, and T4 in patients women compared with the control group. The results show non-significant differences in T3 hormone levels. The results also show a mutation in DNA bands of infertile women compared with fertile control group.